(untitled) (Research, Society and Development, 2021)
Objective: To assess the satisfaction of users attended at the dental school clinic at the Federal University of Campina Grande, Patos/PB, Brazil. Methods: A descriptive cross-sectional study, with a quantitative approach, was carried out starting from a convenience sample of 200 users. The interviews were conducted in a waiting room, using an instrument formulated from the aggregation of previously validated questionnaires: the Oral Health Services Quality Assessment Questionnaire (QASSaB); socio-demographic data and self-perception of oral health. Data were registered in a software and analyzed using descriptive statistics and uni and bivariate inference. Results: There was a profile of female users, with an average age of 37.43 years, married and with a monthly family income above 1 minimum wage and education over 8 years of study, who use the public health service, consider it good their oral health and that they did not present pain of dental origin, in the last 6 months. All dimensions of quality were positively evaluated by users, with a high degree of satisfaction. Only the appointment interval between appointments showed a considerable number of dissatisfaction. Conclusion: The service offered at the clinic-school goes beyond the technical knowledge acquired by academics at the university. The generalist and humanist action follows ethical principles in the health-disease process and satisfactorily and with quality solve the main oral health needs that affect its users.